Mangrove degradation and fish pond expansion analysis in North Kalimantan, Indonesia, using automatic maps of mangroves and shorelines indices - Suyarso; Praditya Avianto (Journal of Water and Land Development)
The east coast of North Kalimantan Province, Indonesia, from the northern border with Sabah, Malaysia, to the south, consists of a series of estuarine landscapes in the north and a delta in the south. Landsat imagery acquired in 1995 shows that there are 150,869 ha of pristine mangrove forest and 14,456 ha of ponds. The mangrove mapping uses the automatic mangrove map and index (AMMI). For ponds mapping, we have introduced the automatic shoreline map (ASM) index, automatic mapping of water body including the shoreline, ponds and rivers. Landsat image from 2000 shows that the mangrove area has decreased to 100,016 ha, while the pond area increased to 27,903 ha. Landsat image from 2010 shows that the mangrove area was 106,867 ha, while the pond area increased to 74,270.2 ha. Landsat imagery from 2022 shows that the remaining mangrove area was 108,187 ha, while the pond area increased further to 84,182 ha. Mangrove decline was extreme from 1995 to 2000, coinciding with Indonesia’s currency crisis. Currency devaluation encouraged local communities and entrepreneurs to create export commodities, with shrimp exports being one of the most promising. To maintain the presence of mangroves, the government implemented a silvo-fishery policy, while farming, it was also restoring mangroves. This paper introduces the fusion of two indices that automatically map mangrove environments to inform multi-temporal changes of mangroves, ponds, and shorelines based on Landsat imagery more accurately, faster, and with lower cost and labour.